مشكلة البطالة عند الشباب الأفغاني وسبل علاجها في ضوء القرآن الكريم والسنة النبوية : دراسة تحليلية - وسيمي، عبد الكريم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
The research aims to study the problem of unemployment among young people in the State of Afghanistan and ways to treat it in the light of the Holy Quran and the Sunnah of the Prophet. As this phenomenon is one of the major problems the Afghan youth suffer from, it has negative and dangerous effects on the individual, family and society levels. Among its most prominent effects are the emergence of extremism and ignorance, poverty and beggary, and the incidence of physical and mental diseases. The Noble Quran and the Sunnah of the Prophet drew the optimal approach to solving the phenomenon of unemployment, as it imposed zakat. Zakat is an important financial tool that can play an important role in treating the phenomenon of unemployment, in terms of stimulating work on the one hand, and in that it is given to the poor and housing to turn them into productive developmental capacity, and that it is an effective tool for fairly distributing money according to priorities and needs. It works to increase Gross national product due to the expansion of the population that pays zakat. Urged charity, permitted good loans, and explained the role of reviving dead land and urging work and lawful earning. The research employed the inductive approach in collecting legal texts from the Quran and Sunnah and relevant sources and references. The research also adopted the analytical method by analyzing the field study results, which aimed to interview university professors and experts. The study sample was conducted in Afghanistan and consisted of 173 participants (168 males and five females) and data were collected using a questionnaire. The results of the questionnaire were analyzed through the technique of calculating proportions (SPSS). The study concluded with a number of results, the most important of which are: There are main reasons for the rise in unemployment, as the paragraph that states (the rule of relations over the law) came in first place with 81.6%. In second place came the paragraph that states (the presence of corruption) with 81%. It came in the last rank, which states (the presence of foreign workers) at 49.4%. In light of these results, the study recommended directing students to the correct and required specializations in the labor market. The study also suggested that training centres be asked to find useful programs and qualifications that meet the job market's needs.